Police responses to Islamist violent extremism and terrorism : a critical analysis - Parsons, Timothy F. (Emerald Publishing Limited, 2024)
Written by a police professional with 40 years' experience, Police Responses to Islamist Violent Extremism and Terrorism examines the evolution of counter-terrorism policy and state narratives on the causes and drivers of Islamist violence and terrorism and issues a direct challenge to the reality they impose on British Muslim communities, as well as the wider British public. Offering an alternative critique, Parsons highlights the benefits of accepting Islamism and Islamists as contributors to British society, whilst advocating for a renewed policy focus on common contributing factors to Islamist violence and terrorism. Examining evolving themes in the ongoing fight against so-called Islamist extremism which have to date often been ignored or minimised by policymakers and academics, the author recognises the vulnerabilities and concerns of Britain's diverse Muslim communities and illuminates areas where a change in policy and approach may deliver better outcomes. Making a clear distinction between what may be characterised by policymakers as extremism, either religious or political, and violent extremism and terrorism, Parsons argues that the former should not be conflated with the latter, a position which is diametrically opposed to much official thought on the subject. Acknowledging successes while also critiquing policy stances and approaches taken by senior police leaders and government policymakers, this richly informed work links professional practice with scholarly research to stimulate debate, discussion and disagreement.